Peridural analgesia with local anesthetics in the implementations of the early recovery protocol after correctable surgery - Jenny Margoth Guacho Guacho; Katia Velázquez González; Ricardo Valdés Lerena; Obdulia Aguado Barrena (Revista Cubana de Anestesiología y Reanimación, 2017)
Introduction: The implementation of an early postoperative recovery protocol guarantees lower morbidity, short postoperative stay, and patient satisfaction. Objectives: To evaluate the usefulness of epidural analgesia within an early recovery protocol in laparoscopic colorectal surgery. Method: A prospective and longitudinal descriptive and observational study was carried out with the objective of evaluating the usefulness of epidural analgesia within an early recovery protocol in laparoscopic colorectal surgery in patients operated at Hermanos Ameijeiras Surgical-Clinical Hospital in the period from May 2014 to December 2016. The sample consisted of 97 patients who underwent laparoscopic colorectal surgery with physical status II-III according to the ASA, of any gender, scheduled for elective laparoscopic colorectal surgery included in the protocol. Results: The average age was 70 years and the male sex predominated. The analgesia obtained was effective, absence of pain was achieved both at rest and in movement at all measurement times in more than 50 % of patients and, when pain appeared, it was considered mild. The requirements for rescue analgesia were 24.7 %. The complications were minimal. Tremors and hypotension appeared in 11.3 % and 9.3 % of cases, respectively. Hospital stay was less than three days in more than half of the patients. Conclusions: The implementation of an early postoperative recovery protocol increases the effectiveness and efficiency in perioperative care.